2020
DOI: 10.3892/mco.2020.2154
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 25 (IL‑25) expression in cholangiocarcinoma

Abstract: Various cytokines are involved in carcinogenesis and tumor progression. Some tumor cells produce cytokines by themselves. Using secretome analysis, a high expression of APEX-1 was found in cholangiocarcinoma (CCA) cell lines. During this secretome analysis, it was found that CCA cell lines overexpressed some cytokines and related molecules, including interleukin 25 (IL-25). In the present study, we first performed precise secretome analysis on cytokines and related molecules in CCA cell lines and identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although these interactions have not been verified experimentally, it is proposed that IL-25 is associated with these factors to mediate EMT in cholangiocarcinoma. 55 In HCC, it has been found that IL-25 was significantly increased in the tissue and serum of patients, and elevated IL-25 expression in the HCC tissue was negatively associated with survival rate and correlated to poor prognosis after radical hepatectomy. 45 Regarding IL-25 involvement in HCC progression, it has been proposed that this cytokine facilitates tumorigenesis via inducing M2 macrophage development through induction of ERK signaling in these cells.…”
Section: Hepatocellular Carcinoma and Cholangiocarcinomamentioning
confidence: 99%
See 3 more Smart Citations
“…Although these interactions have not been verified experimentally, it is proposed that IL-25 is associated with these factors to mediate EMT in cholangiocarcinoma. 55 In HCC, it has been found that IL-25 was significantly increased in the tissue and serum of patients, and elevated IL-25 expression in the HCC tissue was negatively associated with survival rate and correlated to poor prognosis after radical hepatectomy. 45 Regarding IL-25 involvement in HCC progression, it has been proposed that this cytokine facilitates tumorigenesis via inducing M2 macrophage development through induction of ERK signaling in these cells.…”
Section: Hepatocellular Carcinoma and Cholangiocarcinomamentioning
confidence: 99%
“…Moreover, survival analysis discovered that upregulation of IL-25 was associated with shorter survival time in cholangiocarcinoma patients. 55 Further analysis regarding IL-25 involvement in cholangiocarcinoma using protein interaction software STITCH has shown that IL-25 has potential direct and indirect interaction with SMAD2, TGF-β1, NF-κB, and SNAI. It is proposed that SMAD2 and TGF-β1 expression might be involved in IL-25 elevation and EMT.…”
Section: Hepatocellular Carcinoma and Cholangiocarcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from promoting type 2 responses, studies have proved that IL-25 can suppress Th1 and Th17 responses in different environments including the intestine [10][11][12]. Apart from activity in inflammation and allergy reactions, IL-25 also may be involved in tumorigenesis in ways to be explored yet [13,14].…”
Section: Introductionmentioning
confidence: 99%